Response to commentary by Woinarski (Critical‐weight‐range marsupials in northern Australia are declining: a commentary on Fisher et al. (2014) 'The current decline of tropical marsupials in Australia: is history repeating?'). Issue 1 (21st November 2014) - Fisher, Diana O.; Johnson, Chris N.; Lawes, Michael J.; Fritz, Susanne A.; McCallum, Hamish; Blomberg, Simon P.; VanDerWal, Jeremy; Abbott, Brett; Frank, Anke; Legge, Sarah; Letnic, Mike; Thomas, Colette R.; et al.
Abstract The recent commentary by Woinarski (2014, Global Ecology and Biogeography, doi: 10.1111/geb.12165) disagreed with our conclusions on the correlates of decline in the marsupials of tropical Australia (Fisher et al., 2014, Global Ecology and Biogeography, 23, 181–190). We compared traits of species that were associated with range decline in southern and northern Australia. We found that habitat structure, climate and body size were correlated with range decline. In the north, declines of marsupials were most severe in savanna with moderate rainfall. In the south, the ranges of species in open habitat with very low rainfall have declined most. Also, the association between range decline and body mass differed between north and south: this is the main concern of Woinarski, who further disagreed with our choice of the Tropic of Capricorn as a boundary between north and south, our omission of rodents, how to treat timing of extinctions, and our inference that cats are major drivers of decline. We address these concerns in this response.